Enhancing Social Awareness through Total Physical Response (TPR) in Teaching English at Elementary School - Diana, Melani Wahyu; Wilupi, Anis Yona Tyas; Setiawan, Deni; Nurhajati, Diani (English Education:Journal of English Teaching and Research, 2022)
Teachers must equip students with several skills to face global competition in the 21st century. One of these skills is soft skills, one of which is social awareness. Ideally, teaching English to elementary school students should be child-friendly. Learning English in elementary schools trains students to communicate verbally using English in simple conversations and prepares students for social awareness. This study describes the stages in introducing Social Awareness through Total Physical Response (TPR) to teach English in Elementary Schools. This study used a qualitative approach, and the subjects of this study were the fourth grade, fifth, and sixth-grade students. The researchers collected the data by observing offline learning, interviews, and analyzing learning documents, such as textbooks, teaching media, etc. It was found that social awareness can be trained by selecting learning activities and suitable materials for young learners. The selected materials, such as daily activities, hobbies, and professions, give positive examples for the students. Learning activities such as working in-group groups/pairs and the material related to the current situation can improve students' social awareness, such as understanding the problem, empathy, and organization. It proves that TPR can be used to teach English and train the student's social awareness. Keywords:Social Awareness, TPR (Total Physical Response), English Learning